2006
DOI: 10.1128/mcb.00069-06
|View full text |Cite
|
Sign up to set email alerts
|

p53 Downregulates Its Activating Vaccinia-Related Kinase 1, Forming a New Autoregulatory Loop

Abstract: The stable accumulation of p53 is detrimental to the cell because it blocks cell growth and division. Therefore, increases in p53 levels are tightly regulated, mainly by its transcriptional target, mdm2, that downregulates p53. Elucidation of new signaling pathways requires the characterization of the members and the nature of their connection. Vaccinia-related kinase 1 (VRK1) contributes to p53 stabilization by partly interfering with its mdm2-mediated degradation, among other mechanisms; therefore, it is lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(120 citation statements)
references
References 62 publications
4
110
0
6
Order By: Relevance
“…VRK1 downregulation is mediated by p53 transcriptional activation of DRAM (damage-regulated autophagic modulator) [57]. DRAM targets VRK1 to enter in the autophagic pathway [33] and thus be degraded in the lysosome [9,15]. This autoregulatory loop is altered in tumours with p53 mutations [34], resulting in an accumulation of VRK1 protein, which has been detected in human lung [34] and head and neck squamous cell carcinomas [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VRK1 downregulation is mediated by p53 transcriptional activation of DRAM (damage-regulated autophagic modulator) [57]. DRAM targets VRK1 to enter in the autophagic pathway [33] and thus be degraded in the lysosome [9,15]. This autoregulatory loop is altered in tumours with p53 mutations [34], resulting in an accumulation of VRK1 protein, which has been detected in human lung [34] and head and neck squamous cell carcinomas [37].…”
Section: Discussionmentioning
confidence: 99%
“…VRK1 mutants were generated using the Quick-Mutagenesis system (Stratagene, San Diego, CA) and specific primers (indicated in Table S1) following the manufacturer's instructions and using plasmid pCEFL-HA-VRK1 as template. Plasmids expressing full-length human p53 and the mutants R273H, R248H and R280K were obtained from B. Vogelstein (John Hopkins University, Baltimore, USA) and we have used them previously [9,33]. Plasmids expressing GST-p53N-terminal transactivation domains for bacterial expression were obtained from D. Meek (University of Dundee, Scotland) and have been reported before [7] and human GST-p53 fusion proteins 1-390, 90-290 and 290-390 were from T. Kouzaridis (Cancer Research UK, Cambridge).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Recently, the p53-regulated lysosomal degradation of other protein has been reported by Valbuena et al 23 In addition, the role of p53 in the regulation of the lysosomal function has also been reported. 29,30 However, the precise mechanism by which how p53 regulates protein degradation remains unclear.…”
Section: Regulation Of Extracellular Matrix Metalloproteinase Inducermentioning
confidence: 93%
“…It has been reported that p53 is able to modulate degradation of certain proteins via either proteasomal 22 or lysosomal 23 pathway. Therefore, we next sought to determine whether the downregulation of EMMPRIN by p53 occured at protein level.…”
Section: Effects Of P53 Status On Emmprin Protein Expressionmentioning
confidence: 99%